Analisis Kedudukan Waktu dalam Keabsahan Praktek Jual Beli Syariah - Rahmat Hidayat (Institut Agama Islam Negeri Curup, 2019)
This article aims to analyze the position of time and its correlation with sharia sale and purchase transactions, to answer time problems in each component of buying and selling transactions. Buying and selling is a transaction that is most often carried out by humans in meeting their daily needs. One of the main components of buying and selling that distinguishes it from other transactions is the transfer of ownership by handing over the goods with the value of the goods. Normally, the handover of goods occurs in a sale and purchase activity known as the majlis`aqd. However, due to certain factors, the handover may experience delays. A delay or suspension which is a derivative of time has a certain effect on the validity of a sale and purchase contract. So that it can be understood that global universal time has a special position in buying and selling. This research uses content analysis method by making classic and contemporary scholarship books as references plus several journals. This study deduced the opinions of scholars regarding payment or delivery of delayed items which were then analyzed by the authors to be a conclusion. The results of this study indicate that the conditions of time can determine whether or not the sale and purchase agreement is valid. In addition to several aspects, the aspect of clarity of time is very important to note.